TINJAUAN KRITIS TERHADAP RAPERDA MANOKWARI “KOTA INJIL” - Benyamin Malmambessy (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2011)
Monowari’s regulation design ”Bible City” is contibutes some background. In academic copy to be described that judgment importance for is philosophical historical aspect, sosiologis and yudicial formality. Right for Papua society need good been respected in politics, economy, design included culture Monokwari’s regulation intitude city. Concerning regulation design issue that discriminatory, writer recommends so be abolished, as prohibition uses Moslem cloth at common place. Fair regulation design for all Papua society needs to be made by people reconciliation gets religion at Papua.